Transoral Endoscopic Localization of the Parapharyngeal Internal Carotid Artery - Zhang, Guoliang; Zhao, Xia; Sun, Guangbin; Gao, Nan; Yu, Pengcheng; Chen, Zhongchun (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objectives To define transoral endoscopic surgical landmarks for the parapharyngeal segment of the internal carotid artery (ppICA) using cadaveric dissection.Methods Ten fresh cadaveric heads were dissected to demonstrate the parapharyngeal space anatomy and course of the ppICA as seen in a transoral approach. Anatomical measurements of the distance between the ppICA and bony landmarks were recorded and analyzed.Results The stylohyoid ligament, styloglossus, and stylopharyngeus could be considered to be the safe anterior boundary of the ppICA in the transoral approach; among them, the styloid ligament was the most rigid tissue. Dissection between the stylopharyngeus muscle and superior pharyngeal constrictor muscle provides direct access to the ppICA. At the level of the skull base, the distance from the root of the styloid process to the lateral margin of the external aperture of the carotid canal on the left side and on the right side was 8.57 ± 1.97 and 8.80 ± 1.21 mm, respectively. At the level of the maxillary tuberosity, the distance from the ppICA to the maxillary tuberosity on the left side and on the right side was 31.48 ± 2.24 and 31.01 ± 2.88 mm, respectively.Conclusion The endoscopic-assisted transoral approach can facilitate exposure of the ppICA. The root of the styloid process, styloid ligament, and maxillary tuberosity are critical landmarks in the identification of the ppICA in the transoral approach.
Keywords: parapharyngeal internal carotid artery; anatomic landmarks; transoral surgery; endoscope